Problem Solving or Responsibility Avoidance? The Role of CEO Internal Attribution Tendency in Shaping Corporate Downsizing in Response to Performance Shortfalls - Shi, Wei; Chen, Guoli; Li, Boshuo (Journal of Management Studies, 2023)
Abstract This study examines how CEOs' internal attribution tendency – to attribute an observed outcome to internal factors – shapes the extent to which corporate downsizing activities are driven by performance shortfalls. Despite the known effectiveness of downsizing in creating leaner organizations and enhancing firm performance, CEOs often avoid it as it runs counter to their own interests. Applying the awareness‐motivation‐capability (AMC) framework, we argue that CEOs' internal attribution tendency influences their awareness of responsibility for performance shortfalls, and ultimately whether they engage in downsizing actions in response to such shortfalls. This effect becomes more salient when CEOs have the motivation (e.g., scrutiny from financial analysts) or capability (e.g., the existence of an unfavourable external environment) to avoid taking such responsibility. Using a sample of 2424 US firms, we find support for our arguments. Our study highlights the importance of CEO internal attribution tendency in explaining whether firms resort to downsizing actions to address performance shortfalls.